Politik Tata Kelola Bencana: Analisis Kepentingan Antar Aktor dalam Kasus Pengelolaan Bencana Banjir di Kota Medan Tahun 2023 - Depary, Friech Gunana; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2024)
The study of disaster governance analyzes the interests of actors by putting the knowledge of disaster actors or stakeholders as the focus of the study. In the concept of governance, actors in certain domains of government can be referred to as actors, these actors are not necessarily the government, but can also be private, community and other actors. In an effort to minimize the occurrence of flood disasters, the involvement of actors or stakeholders is needed. This research aims to analyze the interests between actors in flood disaster management efforts and the implications of cross-interests in flood disaster management in Medan City. Data collection techniques in this study used observation, interviews and literature studies with qualitative descriptive methods. The results showed that the Government and the Regional Disaster Management Agency of Medan City are the main stakeholders. Then the labosude community, PMI, basarnas, online motorcycle taxi community, PMI, SDABMBK Office are supporting stakeholders. Furthermore, the community as a stakeholder directly affected by the disaster. Actors in flood disaster management have different roles and interests. Each actor in this study has coordinated but in its implementation there are obstacles with the different interests of each actor that occur in convergence and divergence. Then there are limited resources and accurate information in planning and implementing flood disaster management in Medan City and the absence of policies formulated inclusively and deliberatively by the government in disaster management, both before, during and after disasters.